Specific Behavior of Intracellular Streptococcus pyogenes That Has Undergone Autophagic Degradation Is Associated with Bacterial Streptolysin O and Host Small G Proteins Rab5 and Rab7 - Sakurai, Atsuo (American Society for Biochemistry and Molecular Biology, 2010)
Streptococcus pyogenes (group A streptococcus (GAS)) is a pathogen that invades non-phagocytic host cells, and causes a variety of acute infections such as pharyngitis. Our group previously reported that intracellular GAS is effectively degraded by the host-cell autophagic machinery, and that a cholesterol-dependent cytolysin, streptolysin O (SLO), is associated with bacterial escape from endosomes in epithelial cells. However, the details of both the intracellular behavior of GAS and the process leading to its autophagic degradation remain unknown. In this study, we found that two host small G proteins, Rab5 and Rab7, were associated with the pathway of autophagosome formation and the fate of intracellular GAS. Rab5 was involved in bacterial invasion and endosome fusion. Rab7 was clearly multifunctional, with roles in bacterial invasion, endosome maturation, and autophagosome formation. In addition, this study showed that the bacterial cytolysin SLO supported the escape of GAS into the cytoplasm from endosomes, and surprisingly, a SLO-deficient mutant of GAS was viable longer than the wild-type strain although it failed to escape the endosomes. This intracellular behavior of GAS is unique and distinct from that of other types of bacterial invaders. Our results provide a new picture of GAS infection and host-cell responses in epithelial cells.